Understanding Anxiety In Young Efl Learners: A Phenomenal Study - Badda, Abdellah (COMPETITIVE: Journal of Education, 2025)
Learning English as a foreign or a second language has become increasingly valuable. However, the journey of learning can present various challenges. One significant challenge is foreign language anxiety which can affect students, especially when little attention is given to its causes and potential effects. This study aims to explore the possible causes of anxiety in adolescent EFL learners. The research utilizes a qualitative design, collecting data through interviews. A class of 32 young EFL learners participated in a two-hour weekly English session over one school year. At the end of this experience, the students were invited to participate in brief interviews. The information gathered was analysed thematically. The analysis of the students' responses revealed that both girls and boys experience anxiety in the EFL classroom, primarily due to a lack of comprehension, which emerged as a significant cause of their classroom anxiety. Despite the small sample size and specific context, this study offers valuable insights and implications for EFL teachers working with young learners, emphasizing the importance of creating an anxiety-free environment for effective teaching and learning.